Method for constructing heterostructure based on thermotropic electron transfer
By combining alkaline earth metal elements with platinum group metal elements, the heterostructure is constructed by using thermochromic electron transfer, and the bottleneck of single oxide performance and complex problems of multiple oxides is solved, and an efficient and lasting heterostructure is achieved, which is enhanced. Stability and performance retention capability.
Patent Information
- Application Number
- CN202411472079.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-22
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-10-22
AI Technical Summary
Single oxides face performance bottlenecks in practical applications, such as limited activity, large internal transmission resistance, and insufficient stability, making it difficult to meet the requirements of industrial-grade applications for high efficiency and long-lasting. At the same time, various oxides are difficult to exist uniformly during the recombination process, the interface binding force is weak, and they are prone to fall off or phase change, hindering the development and application of high-performance composite oxides.
By combining alkaline earth metal elements with platinum group metal elements, a heterostructure is constructed using thermochromic electron transfer. The specific steps include dissolving alkaline earth metal salt and platinum group metal salt in solvent and mixing, impregnating the substrate, performing unequilibrium instantaneous high temperature treatment, realizing electron reconstruction and lattice distortion, and improving the stability of the connection between the heterostructure and the substrate.
Electronic reconstruction and lattice distortion are realized, and a stable heterostructure with ultra-long load stability and stable performance is constructed, enhancing the stability and performance retention ability of the heterostructure.
Smart Images

Figure CN119392301A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of catalyst preparation, and in particular relates to a method for constructing a heterogeneous structure based on thermally induced electron transfer. Background Art
[0002] Alkaline earth metal oxides mainly include oxides of beryllium, magnesium, calcium, strontium, barium and radium. Alkaline earth oxide materials are regarded as potential candidates in water decomposition electrocatalysts due to their excellent conductivity. They can effectively promote the electron transfer process and accelerate the water molecule splitting reaction. On the other hand, they are also widely used in the field of semiconductor electronic devices. For example: calcium oxide is used as a getter to remove harmful gases in the manufacturing process of semiconductor devices. Barium oxide is used as a photoelectric material to achieve photoelectric conversion or optical signal detection. Strontium oxide can be used in solid capacitors, electronic measuring instruments and other fields. Its high melting point and stability make it an indispensable component of these devices.
[0003] As a sensing material, platinum group metal nanomaterials can accelerate electrode reactions and thus improve sensitivity. When introduced into a suitable solid carrier, it not only acts as a carrier, but also has a significant impact on the surface chemistry and electronic structure, which is conducive to the stable construction of heterogeneous material interfaces and the improvement of electrochemical activity.
[0004] However, single oxides often face performance bottlenecks in practical applications, such as limited activity, large internal transmission resistance, and insufficient stability, making it difficult to meet the stringent requirements of industrial applications for high efficiency and durability. At the same time, multiple oxides face difficulties in the composite process, such as difficulty in coexisting uniformly, weak interface bonding, and easy detachment or phase change under long-term operation. These challenges have seriously hindered the development and application of high-performance composite oxides.
[0005] Based on this, a method for constructing heterostructures based on thermally induced electron transfer is urgently needed. By combining alkaline earth metal elements with platinum group metal elements, electron reconstruction is effectively achieved to form oxide heterostructures. By taking advantage of the difference in thermal expansion between the metal load and the substrate, the material is subjected to non-equilibrium Joule thermal radiation treatment to achieve electron reconstruction and lattice distortion, thereby improving the stability of the connection between the heterostructure and the substrate. Summary of the invention
[0006] In order to solve the above problems, the present invention proposes a method for constructing a heterostructure based on thermally induced electron transfer.
[0007] The present invention relates to a method for constructing a heterostructure based on thermally induced electron transfer, comprising the following steps:
[0008] Step 1: dissolving an alkaline earth metal salt compound and a platinum group metal salt compound in a solvent to prepare two solutions, and mixing the two solutions in equal volumes to prepare a precursor solution;
[0009] Step 2: Immerse the substrate in the precursor solution at room temperature, take it out and dry it to obtain an immersed substrate;
[0010] Step 3: Under normal temperature and air atmosphere, direct current is used to perform non-equilibrium instantaneous high-temperature treatment on the impregnated substrate obtained in step 2 to achieve electron rearrangement transfer and obtain a heterostructure constructed based on thermally induced electron transfer.
[0011] Furthermore, in step 1, the salt compound of the alkaline earth metal is a strontium salt, and the salt compound of the platinum group metal is a ruthenium salt.
[0012] Furthermore, in step 1, the type of strontium salt or ruthenium salt is one of chloride, nitrate, sulfate or acetate.
[0013] Furthermore, in step 1, the concentration of the strontium salt is 0.5 mol / L to 2.0 mol / L, and the concentration of the ruthenium salt is 1 mmol / L to 3 mmol / L.
[0014] Furthermore, in step 1, the solvent is deionized water or ethanol.
[0015] Furthermore, in step 2, the substrate is carbon cloth, carbon paper, nickel foam or nickel mesh.
[0016] Furthermore, in step 2, the substrate is immersed in the precursor solution for 2 minutes to 10 minutes.
[0017] Furthermore, in step 2, the substrate is dried in an air atmosphere at a temperature of 60° C. to 70° C., and the drying time is 1 h to 2 h.
[0018] Furthermore, in step three, the temperature of the non-equilibrium instantaneous high temperature treatment of the substrate is 800° C. to 1000° C., and the treatment time is 1 second to 10 seconds.
[0019] Beneficial Effects
[0020] The present invention designs rapid redox reactions to occur, realizes electronic reconstruction and lattice distortion, constructs a heterostructure of two or more oxides, and ensures that the heterostructure has ultra-long-term load stability and performance stability.
[0021] 1. The present invention effectively realizes electronic reconstruction to form an oxide heterostructure by combining alkaline earth metal elements with platinum group metal elements, thereby enhancing the stability of the heterostructure and achieving ultra-long-term performance retention.
[0022] 2. The present invention utilizes the difference in thermal expansion between the metal carrier and the substrate, and performs non-equilibrium Joule thermal radiation treatment on the material to oxidize the compound and stably recombine it, thereby achieving electronic reconstruction and lattice distortion, and improving the stability of the connection between the heterostructure and the substrate.
[0023] 3. The present invention develops a heterostructured material and its preparation method that can stably coexist with multiple oxide components, has excellent performance and maintains long-term performance stability. It has great scientific significance and practical value for promoting the commercialization of electrocatalytic water decomposition hydrogen production technology, improving the sensitivity of metal oxide-based gas sensitive resistor sensors, and accelerating the rapid development of the semiconductor electronic device industry. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1a This is a microscopic morphology of a heterostructure constructed based on thermally induced electron transfer prepared in Example 1 of the present invention;
[0025] Figure 1b This is a microscopic morphology of a heterostructure constructed based on thermally induced electron transfer prepared in Example 2 of the present invention;
[0026] Figure 1c This is a microscopic morphology of a heterostructure constructed based on thermally induced electron transfer prepared in Example 3 of the present invention;
[0027] Figure 2 The X-ray diffraction (XRD) result diagram of the heterostructure constructed based on thermally induced electron transfer prepared in Examples 1 to 3 of the present invention;
[0028] Figure 3a This is the spectrum of Sr 3d of the heterostructure constructed based on thermally induced electron transfer prepared in Example 1 of the present invention;
[0029] Figure 3b The spectra of C1s and Ru 3d of the heterostructure constructed based on thermally induced electron transfer prepared in Example 1 of the present invention;
[0030] Figure 3c This is a spectrum of Ru 3p in a heterostructure based on thermally induced electron transfer prepared in Example 1 of the present invention;
[0031] Figure 4 This is a polarization curve diagram of a heterostructure constructed based on thermally induced electron transfer prepared in Example 1 of the present invention;
[0032] Figure 5 This is a bar chart of overpotentials of a heterostructure constructed based on thermally induced electron transfer prepared in Example 1 of the present invention;
[0033] Figure 6The long-term stable chronopotentiometry results of the heterostructure constructed based on thermally induced electron transfer prepared in Example 1 of the present invention;
[0034] Figure 7a This is a diagram showing the distribution of alkaline earth metal Sr elements after a long-term stability test of a heterostructure constructed based on thermally induced electron transfer prepared in Example 1 of the present invention;
[0035] Figure 7b This is a diagram showing the distribution of platinum group metal Ru elements in a heterostructure based on thermally induced electron transfer prepared in Example 1 of the present invention after a long-term stability test;
[0036] Figure 7c This is a diagram showing the distribution of O elements in a heterostructure based on thermally induced electron transfer prepared in Example 1 of the present invention after a long-term stability test;
[0037] Figure 7d This is a graph showing the distribution of Ni elements in the substrate of the heterostructure constructed based on thermally induced electron transfer after a long-term stability test prepared in Example 1 of the present invention;
[0038] Figure 8a This is the result of the transmission bright field image of the heterostructure constructed based on thermally induced electron transfer prepared in Example 1 of the present invention under a transmission electron microscope;
[0039] Figure 8b The selected area electron diffraction result of the heterostructure constructed based on thermally induced electron transfer prepared in Example 1 of the present invention under a transmission electron microscope;
[0040] Figure 8c This is a high-resolution transmission electron microscopy image of a heterostructure constructed based on thermally induced electron transfer prepared in Example 1 of the present invention;
[0041] Fig. 9 This is an impedance diagram of a heterostructure constructed based on thermally induced electron transfer prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0042] The present embodiment will be described in detail below with reference to FIGS. 1 to 9 .
[0043] The present invention relates to a method for constructing a heterostructure based on thermally induced electron transfer, comprising the following steps:
[0044] Step 1: Dissolve the salt compound of alkaline earth metal and the salt compound of platinum group metal in solvent to prepare two solutions respectively, and mix the two solutions in equal volumes to prepare a precursor solution.
[0045] The salt compound of the alkaline earth metal is a strontium salt, and the salt compound of the platinum group metal is a ruthenium salt; the type of the strontium salt or the ruthenium salt is one of chloride, nitrate, sulfate or acetate; the concentration of the strontium salt is 0.5mol / L to 2.0mol / L, and the concentration of the ruthenium salt is 1mmol / L to 3mmol / L.
[0046] The solvent used in step 1 is deionized water or ethanol.
[0047] Step 2: Under room temperature, immerse the substrate in the precursor solution, take it out and dry it to obtain an immersed substrate.
[0048] The substrate is carbon cloth, carbon paper, nickel foam or nickel mesh.
[0049] The substrate is immersed in the precursor solution for 2 minutes to 10 minutes.
[0050] The substrate is dried in an air atmosphere at a temperature of 60°C to 70°C, and the drying time is 1h to 2h.
[0051] Step 3: Under normal temperature and air atmosphere, direct current is used to perform non-equilibrium instantaneous high-temperature treatment on the impregnated substrate obtained in step 2 to achieve electron rearrangement transfer and obtain a heterostructure constructed based on thermally induced electron transfer.
[0052] The temperature of the non-equilibrium instantaneous high temperature treatment of the substrate is 800° C. to 1000° C., and the treatment time is 1 second to 10 seconds.
[0053] Embodiment 1
[0054] A method for constructing a heterostructure based on thermally induced electron transfer comprises the following steps:
[0055] Step 1: Dissolve strontium chloride and ruthenium chloride in deionized water to prepare two solutions, and mix the two solutions in equal volumes to prepare a precursor solution.
[0056] The concentration of strontium chloride in the precursor solution is 1.0 mol / L, and the concentration of ruthenium chloride is 3 mmol / L.
[0057] Step 2: Immerse the substrate in the precursor solution for 5 minutes at room temperature, take it out and dry it in an air atmosphere at 60° C. for 2 hours to obtain an immersed substrate.
[0058] The substrate used in step 2 is nickel foam with a size of 2 cm×1 cm×1.6 mm.
[0059] Step 3: At room temperature and air atmosphere, the impregnated substrate is subjected to non-equilibrium instantaneous high temperature treatment using direct current with a voltage of 20 to 30 V and a current of 30 A to 50 A. The treatment temperature is 800° C. and the time is 10 s to obtain a heterostructure constructed based on thermally induced electron transfer.
[0060] Embodiment 2
[0061] The difference between this embodiment and the first embodiment is that the non-equilibrium instantaneous high temperature treatment in step 3 is performed at a temperature of 900° C. The rest is the same as the first embodiment.
[0062] Embodiment 3
[0063] The difference between this embodiment and the first embodiment is that the non-equilibrium instantaneous high temperature treatment in step 3 is performed at a temperature of 1000° C. The rest is the same as the first embodiment.
[0064] Embodiment 4
[0065] The difference between this embodiment and the first embodiment is that the concentration of ruthenium chloride in the precursor solution in step 1 is 1 mmol / L. The rest is the same as the first embodiment.
[0066] Embodiment 5
[0067] The difference between this embodiment and the first embodiment is that the concentration of ruthenium chloride in the precursor solution in step 1 is 2 mmol / L. The rest is the same as the first embodiment.
[0068] Figure 1a This is a microscopic morphology diagram of Example 1 of the present invention. Figure 1b is a microscopic morphology diagram of Example 2, Figure 1c This is the microscopic morphology of Example 3. The microscopic morphology obtained in the results of each example is basically the same, indicating that the change of the highest temperature in the instantaneous high temperature process has little effect on the microscopic morphology. The products obtained by impregnation loading are distributed in dense and uniform small blocks. This morphological feature effectively increases the specific surface area and is conducive to the full occurrence of surface chemical reactions.
[0069] Figure 2 The X-ray diffraction (XRD) result diagram of a heterostructure constructed based on thermally induced electron transfer prepared in Examples 1 to 3. As can be seen from the figure, the samples treated at 800°C, 900°C and 1000°C as the highest instantaneous temperature have the same diffraction peaks, and are consistent with JDPDS cards 21-1172RuO2 and 01-1113SrO2, indicating that the oxides are successfully prepared and coexist through short-term high-temperature environment thermal radiation to form a heterostructure.
[0070] FIG3 is an X-ray photoelectron spectroscopy (XPS) result diagram of a heterostructure constructed based on thermally induced electron transfer prepared in Example 1. The metal element contained in the precursor solution is marked in the lower left corner of the sample in each figure, and the single metal element is a comparison sample. Figure 3a is the Sr 3d spectrum. Example 1 and the comparative sample both show two peaks, corresponding to Sr 2+ 3d 3 / 2 and Sr 2+ 3d 5 / 2 In the comparison sample in which the metal element in the precursor solution is only Sr, the corresponding binding energies of the two peaks are ~135.89eV and ~134.11eV, while in the sample after adding Ru, that is, in Example 1, the peak position of Sr 3d has a significant negative shift, and the binding energies are located at ~134.77eV and ~133.04eV, respectively. Figure 3a This indicates that the valence state of Sr in the heterostructure is reduced, and there is a certain tendency to gain electrons. The addition of platinum group elements regulates the electron distribution of the heterostructure.
[0071] Figure 3b The following are the spectra of C1s and Ru 3d. Since the test requires the addition of a certain amount of C to the sample surface for calibration, all samples show characteristic C1s signals, which contain three peaks belonging to O–C–O (~289.31 eV), C=O (~286.12 eV) and C–C (~284.80 eV). Figure 3b The peak position of Ru 3d in Example 1 is obviously positively shifted compared with the comparative sample. The fitting results show that ~282.21eV and ~278.99eV correspond to Ru 0 3d 3 / 2 And Ru 0 3d 5 / 2 In addition, ~283.01eV and ~280.47eV correspond to Ru 4+ 3d 3 / 2 And Ru 4+ 3d 5 / 2 .
[0072] Figure 3c The Ru 3p spectrum of Example 1 can be fitted into four peaks with binding energies of ∼484.07 eV and ∼461.66 eV, corresponding to Ru 0 3p 1 / 2 And Ru 0 3p 3 / 2 , the binding energies are ~485.89eV and ~463.85eV, corresponding to Ru 4+ 3p 1 / 2 And Ru 4+ 3p 3 / 2 .
[0073] comprehensive Figure 3b and Figure 3c The results show that Ru in the sample does not exist as a pure element, but as a high-valent Ru. 3+ From the analysis of the results from the state to transient high-temperature treatment, it can be seen that in the non-equilibrium transient high-temperature process, both oxidation and reduction processes occur, and the electron transfer process obviously exists, constructing a heterogeneous structure and enriching the valence state and ionic state of Ru.
[0074] Figure 4 This is a polarization curve diagram of a heterostructure constructed based on thermally induced electron transfer prepared in Example 1; Figure 5 This is a bar chart of the overpotential of the heterostructure based on thermal electron transfer prepared in Example 1. The heterostructure was analyzed by chronopotentiometry in 1M KOH electrolyte. For the OER reaction, 10 mA / cm 2 The current density only requires an overpotential of 199.84 mV, indicating that the composite heterostructure of multiple oxides as an electrocatalyst effectively reduces the overpotential of the water electrolysis reaction and reduces energy consumption. Figure 4 and Figure 5 The data results fully demonstrate that the heterostructure prepared by the method of Example 1 can be effectively applied in the field of electrocatalysis.
[0075] Figure 6 The long-term stability test results of the heterostructure based on thermal electron transfer prepared in Example 1 are shown in Figure 1. To verify the service stability of the heterostructure, the constant current density (10 mA cm -2 ) were collected under chronopotentiometry. Since the reaction process consumes electrolyte, the arrow in the figure indicates the electrolyte replenishment point. The electrolyte is replenished about every 900 hours on average to ensure the continuous reaction. The potential is stable at 1.575V vs. RHE, and the performance lasts for at least 3790 hours (about 157 days), indicating that the heterostructure has good electrochemical performance stability.
[0076] FIG. 7 is a surface scanning energy spectrum result of the heterostructure constructed based on thermally induced electron transfer prepared in Example 1 after a long-term stability test. Figure 7a It is the result of the distribution of the alkaline earth metal Sr element. The Sr element still exists and is evenly distributed. Figure 7b It is the distribution result of the platinum group metal Ru element. The Ru element has been confirmed to exist and its distribution is also uniform. Figure 7c It is the distribution result of O element. O element exists and is evenly distributed. Figure 7dThe distribution of Ni element in the substrate is a result of uniform distribution, which proves the integrity of the substrate material. The results of continuous and long-term constant current tests prove that the heterogeneous structure formed by the prepared alkaline earth metal oxide and platinum group metal oxide has a stable load and will not change or fall off due to the reaction.
[0077] FIG8 is a characterization result of a heterostructure constructed based on thermally induced electron transfer prepared in Example 1 under a transmission electron microscope. Figure 8a is the transmission bright field image result. Figure 8a It can be seen that the sample has a nanorod morphology with a diameter of about 30 nm, and the rod-like structure has good homogeneity.
[0078] Figure 8b The result of selected area electron diffraction is a circular ring, which is a characteristic of polycrystalline. The diffraction rings in the figure (from inside to outside) can be attributed to the (0 0 2) and (1 0 3) crystal planes of SrO2, and the (2 2 0) and (3 0 1) crystal planes of RuO2, which further confirms the presence of both alkaline earth metal oxides and platinum group metal oxides in the sample phase.
[0079] Figure 8c It is a high-resolution transmission electron microscopy image. As can be seen from the figure, by calculating the crystal planes of different orientations in the same selected area, it can be obtained that the crystal plane spacing of 0.330nm comes from the (0 0 2) plane of SrO2, and the lattice spacing of 0.317nm corresponds to the (1 1 0) plane of RuO2, further confirming the formation of oxide heterostructures.
[0080] The characterization results in Figure 8 show that the heterostructured material presents a nearly parallel nanorod morphology arranged in the same direction, which effectively increases the microscopic specific surface area, exposes more active sites, and is conducive to improving the efficiency of material transfer. The nanorods have a large overall connection site with the substrate, which ensures that the load is stable and not easy to fall off.
[0081] Fig. 9 This is the impedance diagram of the heterostructure based on thermal electron transfer prepared in Example 1. The sample names in the figure are the metal elements contained in the precursor solution, and the single metal element is the comparison sample. The charge transfer resistance can be reflected by the impedance diagram. At the open circuit potential, the larger the slope of the curve in the figure, the smaller the transfer impedance. Fig. 9 As shown in the figure, the impedance curve slope of the heterostructure formed by multiple oxides is larger, indicating that the design of the heterogeneous interface reduces the interface charge transfer resistance and is more conducive to charge transfer. Secondly, a small change in the impedance itself can significantly affect the output signal, so a smaller initial impedance can increase the sensitivity of the gas resistor sensor to changes in gas concentration. Smaller self-resistance expands the adjustment range and is also conducive to more precise adjustment of resistance, improving sensing accuracy.
[0082] The above contents of the present invention are only preferred embodiments of the present invention and are not intended to limit the implementation scheme of the present invention. A person skilled in the art can easily make corresponding changes or modifications based on the main concept and spirit of the present invention. Therefore, the protection scope of the present invention shall be based on the protection scope required by the claims.
Claims
1. A method for constructing a heterostructure based on thermally induced electron transfer, characterized in that: The steps include: Step 1: dissolving an alkaline earth metal salt compound and a platinum group metal salt compound in a solvent to prepare two solutions, and mixing the two solutions in equal volumes to prepare a precursor solution; Step 2: Immerse the substrate in the precursor solution at room temperature, take it out and dry it to obtain an immersed substrate; Step 3: Under normal temperature and air atmosphere, direct current is used to perform non-equilibrium instantaneous high-temperature treatment on the impregnated substrate obtained in step 2 to achieve electron rearrangement transfer and obtain a heterostructure constructed based on thermally induced electron transfer.
2. The method for constructing a heterostructure based on thermally induced electron transfer according to claim 1, characterized in that: In step 1, the salt compound of the alkaline earth metal is a strontium salt, and the salt compound of the platinum group metal is a ruthenium salt.
3. The method for constructing a heterostructure based on thermally induced electron transfer according to claim 2, characterized in that: In step 1, the type of strontium salt or ruthenium salt is one of chloride, nitrate, sulfate or acetate.
4. The method for constructing a heterostructure based on thermally induced electron transfer according to claim 2, characterized in that: In step 1, the concentration of the strontium salt is 0.5 mol / L to 2.0 mol / L, and the concentration of the ruthenium salt is 1 mmol / L to 3 mmol / L.
5. The method for constructing a heterostructure based on thermally induced electron transfer according to claim 1, characterized in that: In step 1, the solvent is deionized water or ethanol.
6. The method for constructing a heterostructure based on thermally induced electron transfer according to claim 1, characterized in that: In step 2, the substrate is carbon cloth, carbon paper, nickel foam or nickel mesh.
7. The method for constructing a heterostructure based on thermally induced electron transfer according to claim 1, characterized in that: In step 2, the substrate is immersed in the precursor solution for 2 minutes to 10 minutes.
8. The method for constructing a heterostructure based on thermally induced electron transfer according to claim 1, characterized in that: In step 2, the substrate is dried in an air atmosphere at a temperature of 60° C. to 70° C., and the drying time is 1 hour to 2 hours.
9. The method for constructing a heterostructure based on thermally induced electron transfer according to claim 1, characterized in that: In step three, the substrate is subjected to non-equilibrium instantaneous high temperature treatment at a temperature of 800° C. to 1000° C., and the treatment time is 1 second to 10 seconds.
Citation Information
Patent Citations
Method for rapidly preparing cobalt-based ultrathin two-dimensional nano array electrocatalyst
CN117070993A
Method for rapidly synthesizing heterostructure electrocatalyst through Joule heat and application
CN117821995A
Preparation method and application of calcium manganese oxide electrocatalyst based on bionic photosynthesis design
CN118186399A
Method for preparing ferric oxide-based supercapacitor negative electrode material through thermal shock
CN118762940A